Konseling Person Centered Therapy dalam Meningkatkan Kepercayaan Diri Mahasiswa Berkebutuhan Khusus Cerebal Palsy - Rischa Pramudia Trisnani; M. Ramli; Carolina Ligya Radjah (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2021)
Students with Special Needs Cerebral Palsy are individuals who take higher education but experience deviation in motor function, especially movement of muscles and have obstacles in the development of motion, causing limited activity. The purpose of this study was to increase the self-confidence of students with special needs Celebral Palsy through Person Centered Therapy counseling. This research is a type of qualitative research with a case study method. The subject of this research is students with special needs Celebral Palsy with the initials